The Psychometric Properties of the Norwegian version of Parental Stress Scale (PSS) - Kornør, Hege; Richter, Jörg (PsykTestBarn, 2013)
Description: The Parental Stress Scale (PSS) is an 18-item parent-report questionnaire to assess stress levels associated with parenting. The US researchers Judy O. berry and Warren H. Jones published the instrument in 1995. Ane Nærde from The Norwegian Center for Child Behavioral Development has translated the PSS into Norwegian. There is no information available on copyright. Completion time and user qualification requirements are unknown. Literature search: None of the 51 identified references met our inclusion criteria. Conclusion: The psychometric properties of the Norwegian version of the Parenting Stress Scale are unknown. It should not be used clinically until Norwegian psychometric data is available.